PENGARUH PENERAPAN INFORMASI AKUNTASI, PARTISIPASI DAN KEPUASAN KERJA TERHADAP KINERJA MANAJER HOTEL DI SURAKARTA - Jumingan, Jumingan (STIE Atma Bhakti, 2019)
The purpose of this study was to determine the effect of the application of accounting information, participation in job satisfaction and joint or simultaneous influence between the application of accounting information, participation in the use of accounting information and job satisfaction on manager performance. The hypothesis proposed as follows is assumed to have a significant influence between the application of accounting information to the performance of functional managers of 3 and 4 star hotels in the Surakarta region. The population in the study were all functional hotel managers of 3 and 4 star hotels in the Surakarta region, while the samples taken were 50 hotel functional managers with sampling techniques using the stratified random sampling method. Analysis of the data used in this study are: validity test, reliability test, partial regression analysis, t test, multiple linear regression analysis, F test, and coefficient of determination (R2). Based on the results of the analysis it can be concluded that the application of accounting information, participation and job satisfaction proved to influence the performance of managers both partially and jointly or simultaneously and the results of the coefficient of determination analysis found that the application of accounting information, participation and job satisfaction had an influence on manager performance amounting to 81.1%.